ANALISIS PERMASALAHAN SOSIAL PADA MASYARAKAT BALI DALAM CERPEN CETIK KARYA PUTU DESSY SAVITRI DEWI - Andre Aditya, Gede; Gek Intan, Ni Nyoman; Nanda Defhayana, I Komang Tri; Ayu Diah Rukmayanti, Ni Nyoman; Susanthi Pradnya Paramitha, Ni Made Ayu (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2024)
Social problems are conditions that are not expected to occur in society. This study aims to describe social problems in the short story Cetik by Putu Dessy Savitri Dewi. The benefits of analyzing short stories are very diverse, from the first not knowing to knowing, those who do not understand to understand. Writers and readers will very easily understand the content contained in a short story, especially for people who like short stories. The methods used in this study are descriptive analytics and recording techniques. The results and discussion of this research show that social problems in Balinese society that can be collected in the short story are problems in poverty, problems in religion and belief, greed for positions and social life of the Balinese people. Thus, the existence of the short story Cetik by Putu Dessy Savitri Dewi shows the problems that occur in Balinese society.